Pengaruh Kecerdasan Emosional, Stres Kerja, dan Learning Organization terhadap Kinerja Perawat dengan Kepuasan Kerja sebagai Variabel Mediasi (Studi pada Rumah Sakit Wiyung Sejahtera Surabaya) - Yuzril Farizyal Baharuddin; Dewi Nuraini (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to examine the effects of emotional intelligence, job stress, and learning organization on job performance with job satisfaction as a mediating variable among nursing staff at Wiyung Sejahtera Hospital Surabaya. A quantitative approach with a survey method was employed. The sample consisted of 127 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings indicate that emotional intelligence and learning organization have positive and significant effects on job satisfaction and job performance, while job stress has a negative and significant effect on both variables. Furthermore, job satisfaction positively and significantly influences job performance. The mediation analysis reveals that job satisfaction significantly mediates the relationships between emotional intelligence, job stress, and learning organization with job performance. These findings support the Job Demands-Resources Theory, suggesting that personal and organizational resources enhance job satisfaction and performance, whereas excessive job demands reduce both outcomes.